A Preliminary Review of Allium subg. Melanocrommyum in Central Asia - Fritsch, Reinhard M. (e!DAL - Plant Genomics and Phenomics Research Data Repository (PGP), IPK Gatersleben, Seeland OT Gatersleben, Corrensstraße 3, 06466, Germany, 2016)
The review (288 pages A4) contains a taxonomic treatment of subg. Melanocrommyum (82 species and subspecies with about 40 synonyms, but no new taxa) affiliated to 17 sections and 21 subsections. Included is also subg. Porphyroprason (1 species, 2 synonyms). The publication starts with a Foreword, a General Introduction into the biological features of subg. Melanocrommyum, and an illustrated key (in color) for determination simultaneously in English and Russian on opposite pages. In the Taxonomy chapter, the complete synonymy (according to the current rules of botanical nomenclature) with data of types and paratypes, the known distribution, a detailed morphological description, a plate composed of several color photographs, karyological data available from the literature and own observations, the offspring of the living material studied, taxonomic remarks (including a detailed discussion of molecular results), biological data, and economic traits are presented for every species and subspecies as far as data were available or were published in the literature. A comprehensive List of References and an Index of Scientific and Folk's names plus more general terms complete the volume. A list of herbarium vouchers seen and some original karyological data are added as appendices.
Keywords: Allium subg. Melanocrommyum; Central Asia; Kazakhstan; Kyrgyzstan; Tajikistan; Turkmenistan; Uzbekistan; Taxonomy; Description; Nomenclature; Key for Determination; Distribution; Morphology; Biological Data; Economic Traits; Karyology